Application of Family Psychoeducation to Client Psychosocial Disorder Anxiety and Body Image Due - Hasmira Hasmira; Budi Anna Keliat; Giur Hargiana (Jurnal Keperawatan Jiwa (JKJ): Persatuan Perawat Nasional Indonesia, 2020)
Diabetes mellitus is a metabolic disease that is becoming poses a threat to global health and requires special attention. The prevalence of Diabetes mellitus has increased significantly throughout the world in the last 10 years. Indonesia ranks sixth among people with diabetes worldwide. Anxiety and body image are of the psychosocial effects given from Diabetes mellitus. Anxiety and body image can affect the client’s diet, causing changes in nutrition. Through case report by providing family psychoeducation therapy in the form of stress management that can reduce and even overcome anxiety and body image is very useful for clients and families to reduce the risk of body image for clients who experience nutritional imbalances and family body image that treats clients with Diabetes mellitus. This study aims help to overcome anxiety and body image disorders in diabetes mellitus clients so that diabetes mellitus clients have a good appetite. In addition, families are also able to cope with stress in treating diabetes mellitus clients. Research using case studies shows that clients already have a good appetite, anxiety and impaired body image can be lowered and the family is able to cope with stress and able to treat clients with diabetes mellitus. Family psychoeducation therapy is very useful in reducing the level of anxiety and disruption of the body image of a diabetes mellitus client in supporting the client’s diet and being able to deal with family stress in caring for a diabetes mellitus client.